Aggregation and conformational change of mushroom (Agaricus bisporus) polyphenoloxidase subjected to thermal treatment. (1st January 2017) - Zhou, Lei; Liu, Wei; Zou, Liqiang; Xiong, Zhiqiang; Hu, Xiuting; Chen, Jun
Highlights: Both high temperature-short time and mild temperature-long time can inactivate PPO. PPO samples with the same activity were obtained by different thermal treatment. PPO with the same activity might possess different conformations. Mild temperature deformed PPO, while high temperature induced aggregation of PPO. Abstract: This study investigated changes in the activity, conformation and microstructure of mushroom polyphenoloxidase (PPO) subjected to thermal treatment. The inactivation of PPO can be achieved by high temperature-short time or mild temperature-long time treatment. Circular dichroism and fluorescence spectra suggested that heating process induced the rearrangement of secondary structure and the disruption of tertiary structure. Red shifts of fluorescence spectra showed positive correlations with the inactivation rate of PPO. There were significant differences in the conformation and molecular microstructure among PPO samples with the same relative activity, which were obtained by treating PPO at 45, 55 and 65 °C for different times. In summary, PPO molecules were deformed at mild temperature, while higher temperature induced the formation of large aggregates. PPO with the same relative activity might exist in different forms.